(NsOKROWI]A MIROWOJ VIWOPISIs (NISSKUSSTWAs - (No(B.(Nw(B.(NmOROZOWA(B.s; (Ne(B.(Nn(B.(NeWRATOWAs; (Ne(B.(Nwg(B.(NOROMOWAs ((NmOSKWAs (NaBRISs, 2019)
(NzA MNOGOWEKOWU@ ISTORI@ VIWOPISI BYLO SOZDANO WELIKOE MNOVESTWO KARTIN(B.s